2019
DOI: 10.1016/j.colsurfb.2018.09.080
|View full text |Cite|
|
Sign up to set email alerts
|

Incorporation of functionalized carbon nanotubes into hydrophobic drug crystals for enhancing aqueous dissolution

Abstract: We present for the first time the direct incorporation of carboxylated carbon nanotubes (f-CNTs) into hydrophobic drug particles during their formation via anti-solvent precipitation. The approach was tested using two drugs namely antifungal agent Griseofulvin (GF) and antibiotic Sulfamethoxazole (SMZ) that had very different aqueous solubility. It was observed that the f-CNTs dispersed in the water served as nucleating sites for crystallization and were readily incorporated into the drug particles without alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Carboxylated multiwall carbon nanotubes were synthesized following a methodology published previously in [51]. CNTs were reacted with a mixture of concentrated sulfuric acid and nitric acid at 140 • C for 5, 10, and 40 minutes, respectively, in a microwave reactor (model: CEM Mars).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboxylated multiwall carbon nanotubes were synthesized following a methodology published previously in [51]. CNTs were reacted with a mixture of concentrated sulfuric acid and nitric acid at 140 • C for 5, 10, and 40 minutes, respectively, in a microwave reactor (model: CEM Mars).…”
Section: Methodsmentioning
confidence: 99%
“…Among functionalized CNTs, carboxylated CNTs (f-CNTs) are highly water dispersible and our studies have demonstrated their potential to enhance dissolution rates [51]. F-CNTs can be synthesized so that the carbon to oxygen atomic ratio can be varied to give different levels of hydrophilicity and it is conceivable that by varying the degree of functionalization, the drug can be released at different rates.…”
Section: Introductionmentioning
confidence: 99%
“…The time necessary to reach 80% dissolution (t 80 ) of the drugs decreased from 67 to 10 min with the incorporation of 5.1% of f-CNTs in the case of SMZ. For GF, the decrease was from 66 to 18 minutes with the addition 4% of f-CNTs (Figure 17) [24].…”
Section: Miscellaneousmentioning
confidence: 99%
“…14,15 The binding of drugs on MWCNT has been extensively studied in recent years, showing that this type of formulation is one of the most promising alternatives to treat HAI. [16][17][18] However, it is well known that MWCNTs possess intrinsic toxicity under certain conditions and characteristics, which are reduced by functionalization, considerably improving their solubility in various media, increasing their bioavailability and biocompatibility. [19][20][21] MWCNTs have been covalently bounded with different conventional antibiotics and organic compounds such as ionic liquids for antibacterial purposes.…”
Section: Introductionmentioning
confidence: 99%